Electrical Resistivity Imaging (ERI) for Identifying Near-surface Bodies at Diyala University site, NE of Iraq - Shamkhi, Mustafa T.; Karim , Hussein H. (Iraqi Journal of Science, 2022)
The current research demonstrates the ERI method’s effectiveness as a supplementary engineering site investigation approach. Engineering site research is important to indicate the subsoil of proposed production sites. The benefit of the dipole-dipole array for ERI electrical resistivity imaging is that it provides informative records of subsurface geology and condition along with profiles. The dipole-dipole array was performed along with three parallel profiles at the Diyala University site to identify the buried facilities (pipes and cables) in the area. The buried electric cable embedded in a plastic tube was used for simulation to report and verify the field resistivity results. Interpretation of field facts confirmed that the used ERI method was robust in locating buried structures. The dipole-dipole array’s strong horizontal sensitivity to subsurface resistivity releases made it possible to provide greater certainty of site characteristics concerning the buried systems. The results were consistent with the information on wells near the work site.